TRADISI TEPUK TEPUNG TAWAR DALAM PERSPEKTIF HUKUM ISLAM: (Studi Kasus di Kecamatan Bengkalis) - Husnah; Dewi, Irlina; Fajaruna, Eva (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2023)
This research explains the local wisdom of Malay culture regarding the plain flour pate which is a traditional Malay procession that is encountered at every ceremony carried out by the Malay community which has Islamic meaning and symbols in it. The purpose of this study was to find out the perspective of Islamic law on the plain flour pate tradition and to find out the philosophical meaning contained in the materials used in the plain flour pate tradition. This tradition also has the function of offering prayers. The method used in this research is field research where data can be obtained through interviews and documentation. This tradition also has the function of offering prayers. The method used in this research is field research where data can be obtained through interviews and documentation. The results of the study show that the plain flour patting tradition does not conflict with Islamic law, this is because the activities of the plain flour patting tradition have meaning in giving prayer and gratitude to Allah SWT. The philosophical meaning contained in the traditional material of plain flour pate which is used in all traditional ceremonies is not contrary to the teachings of the Islamic religion, this is because all the materials used have meanings that reflect Islamic values, as is the case with white rice which has the meaning of purity, turmeric rice has the meaning of marwah which is not extinct, perfume which has the meaning of the fragrance of marwah, bertih has the meaning of sharing together, henna leaves symbolize harmony and potpourri which means inner and outer purity.